PENGARUH MENSTRUASI TERHADAP MINAT SISWA PUTRI DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA PUTRI KELAS X SMA NEGERI 1 BANGIL ) - PRAHASTINI, NOVITA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Interest factor will give big effect to student learning process. Interest will encourage student learning better than without interest. During following physical education, movement limitation indirectly can affect student interest. Just like female student who think that menstruation as something that can limit their activity, especially during following physical education learning. During this time at school often seen female student that not following physical education with various reasons like stomach ache, worried, and uncomfort so that they reluctant to performed physical education.  This research aim to find out the effect of menstruation to female student interest on physical education. This is a qualitative research with descriptive qualitative method. Subject in this research is female student of SMA Negeri I Bangil that amounted of 10 students. While the process data collecting conducted by guided free interview on each subject.   Research results that obtained : from 10 respondents, each experienced emotional disorder during menstruation, both pain that caused by menstruation or cautious and anxious due affraid to soaked that cause student to lazy to move and tend to rest. Thus, menstruation can alter female student interest in following physical education, that at first have high interest in following the lesson become decrease. So, there is an effect of menstruation to female student interest in following physical, sports and health education learning. Keywords:menstruation, interest, physical sport, and health education.